2009
DOI: 10.1115/1.3197562
|View full text |Cite
|
Sign up to set email alerts
|

Predicted Efficiency of a Low-Temperature Nanofluid-Based Direct Absorption Solar Collector

Abstract: Due to its renewable and nonpolluting nature, solar energy is often used in applications such as electricity generation, thermal heating, and chemical processing. The most cost-effective solar heaters are of the “flat-plate” type, but these suffer from relatively low efficiency and outlet temperatures. The present study theoretically investigates the feasibility of using a nonconcentrating direct absorption solar collector (DAC) and compares its performance with that of a typical flat-plate collector. Here a n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
227
2
5

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 578 publications
(257 citation statements)
references
References 17 publications
0
227
2
5
Order By: Relevance
“…The steam thus generated is usually in thermal equilibrium with the bulk liquid. Nanofluids-fluids seeded with nanoparticles-as another alternative have been studied [5][6][7] as volumetric absorbers, potentially minimizing the surface energy loss by uniform temperature in the fluid 6 and enhanced thermal conductivity of nanofluid 8,9 . Local generation of steam in a cold bulk liquid can be achieved through high concentrations or illumination of nanofluids by electromagnetic waves (generally, lasers) with high power intensity [10][11][12][13][14][15][16][17][18] .…”
mentioning
confidence: 99%
“…The steam thus generated is usually in thermal equilibrium with the bulk liquid. Nanofluids-fluids seeded with nanoparticles-as another alternative have been studied [5][6][7] as volumetric absorbers, potentially minimizing the surface energy loss by uniform temperature in the fluid 6 and enhanced thermal conductivity of nanofluid 8,9 . Local generation of steam in a cold bulk liquid can be achieved through high concentrations or illumination of nanofluids by electromagnetic waves (generally, lasers) with high power intensity [10][11][12][13][14][15][16][17][18] .…”
mentioning
confidence: 99%
“…The efficiency of a solar thermal receiver is the ratio of collected thermal energy to the total incident energy (Tyagi et al, 2009) …”
Section: Receiver Optimizationmentioning
confidence: 99%
“…Kumar and Tien (1990) developed a model for particle-laden falling liquid films (1-5 mm thick) incorporating the spectral and directional radiative properties of the particles, and provided a framework for future modeling studies. More recently, Tyagi et al (2009) numerically investigated a low temperature nanofluid receiver inside a mini-channel; while, Otanicar et al (2009b) extended this model to include multiple and dependent scattering, and size-dependent optical properties. Otanicar et al (2010) also experimentally demonstrated the use of different nanofluids in a micro-channel solar collector.…”
Section: Introductionmentioning
confidence: 99%
“…Tyagi investigated the efficiency of a direct absorption solar collector containing nanofluids under numerical comparison with a conventional flat plate collector. He used aluminum nanoparticles, and in this collector model, he showed that performance under normal operations was almost 10% more than performance of the conventional flat plate collector under similar conditions [2]. Otanicar carried out an experimental study on the effects of using nanofluids in a microsized direct absorption collector and showed that it had a positive effect of about 5% on collector efficiency [3].…”
Section: Introductionmentioning
confidence: 99%